High-surface-roughness anion exchange membrane based on radiation grafting and preparation method thereof

By introducing quaternary ammonium-based cationic groups and aromatic side chains on the anion exchange membrane using radiation grafting technology, a film with high surface roughness is formed, which solves the problems of low conductivity and poor alkali stability of the anion exchange membrane, and significantly improves its performance in hydrogen production through electrolytic water.

CN119499892AActive Publication Date: 2025-02-25TIANJIN UNIV
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411466862.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-25
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

The anion exchange membrane faces the problems of low conductivity and poor alkali stability during the electrolysis process of hydrogen production, which affects its performance.

Method used

Using a radiation grafting process, an anion exchange membrane with high surface roughness is formed by using polyethylene, polypropylene, etc. as the main chain and introducing quaternary ammonium cationic groups and aromatic side chains thereon.

Benefits of technology

The mechanical properties, conductivity and chemical stability of the anion exchange membrane are improved, and its adhesion to the catalytic layer and contact area are enhanced, thereby improving the performance of hydrogen production by electrolyzing water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119499892A_ABST
    Figure CN119499892A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of anion exchange membranes, and discloses a radiation-grafting-based anion exchange membrane with high surface roughness and a preparation method thereof, polyethylene (PE), polypropylene (PP), ethylene tetrafluoroethylene (ETFE), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE) and the like are used as main chains, aryl side chains containing quaternary ammonium cation groups are adopted, and the radiation-grafting-based anion exchange membrane with high surface roughness is prepared. A novel anion exchange membrane material is synthesized through a radiation grafting process, so that the anion exchange membrane material has relatively high mechanical property, conductivity and chemical stability; meanwhile, the material has higher surface roughness, so that the material has higher hydrophilicity, higher adhesion to a catalyst layer and larger contact area with the catalyst layer, thereby having more excellent fuel cell and water electrolysis performance; in addition, the synthesis method is relatively simple in overall process, mild in reaction condition, relatively short in reaction time, relatively low in cost and easy for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anion exchange membranes, and in particular relates to an anion exchange membrane based on radiation grafting and a preparation method thereof. Background Art

[0002] Despite the continuous increase in proven oil and gas reserves, the non-renewable and rapid consumption of fossil fuels may not be enough to meet future energy needs, resulting in a gap between energy supply and demand in the near future, thus threatening the world's energy security. In recent years, many countries and companies have invested heavily in extensive research and development programs to develop new alternative and renewable energy sources and technologies that can bridge the current and future energy supply shortages in a sustainable way. New energy sources include hydropower, wind power, solar power, geothermal energy, biomass energy, nuclear energy and hydrogen energy, and of course fuel cell technology and water electrolysis technology. Hydrogen energy is the most promising green and clean alternative energy in the future, with the advantages of low carbon emissions, no pollution and high efficiency.

[0003] Alkaline electrolysis of water to produce hydrogen (AEMWE) has always attracted much attention due to its many advantages such as low cost and the use of non-precious metal catalysts. Anion exchange membranes (AEMs) are key components of electrolytic cells and are composed of a polymer skeleton and cationic groups. The role of AEMs is to convert OH - O2 is produced by transferring from the cathode side to the anode side, separating the gases produced by the positive and negative electrodes. The polymer backbone determines the mechanical strength of the membrane, and the cationic group is responsible for transferring OH - ions. However, AEMs face the problem of relatively low ion exchange rate. In addition, alkaline anion exchange membranes also face the problem of relatively poor alkaline stability. The main chain and quaternary amine groups in the polymer chain structure are easily affected by strong alkaline nucleophiles OH - The attack of ions leads to the degradation of the main chain and quaternary amine groups, which damages the AEM and reduces the ion transport capacity. Therefore, improving the conductivity and alkaline stability of anion exchange membranes and optimizing their application in electrolyzed water are urgent issues that need to be addressed by anion exchange membranes.

[0004] There is currently little research on the effect of surface roughness of anion exchange membranes on hydrogen production by water electrolysis. Since roughness is closely related to the degree of surface area expansion, it will affect the contact angle (CA) and adhesion of the liquid (Industrial & Engineering Chemistry, 1936, 28 (8): 988-994.). Generally, surface structures with greater roughness have a larger specific surface area, providing more contact points for intermolecular interactions (Nature communications, 2021, 12 (1): 1477.), which may increase adhesion. The surface roughness of AEM may affect the interface between AEM and the catalyst layer. In addition, more contact points will also increase the number of ion transmission channels, thereby improving the performance of AEMWE.

[0005] Therefore, in order to address the problems of improving the conductivity and alkaline stability of the above-mentioned anion exchange membrane and explore the influence of the surface roughness of the anion exchange membrane on the performance of hydrogen production by electrolysis of water, the present invention proposes an anion exchange membrane with high surface roughness based on radiation grafting. The present invention uses polyethylene (PE), polypropylene (PP), ethylene tetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE) and the like as the main chain, and adopts aromatic side chains containing quaternary ammonium cationic groups to have higher mechanical properties, conductivity and chemical stability; and the present invention has a higher surface roughness, so that it can perform better in the electrolysis of water test. Summary of the invention

[0006] The present invention focuses on solving the problems of anion exchange membranes needing to improve conductivity and alkaline stability, and provides an anion exchange membrane with high surface roughness based on radiation grafting and a preparation method thereof. The present invention uses polyethylene (PE), polypropylene (PP), ethylene tetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE) and the like as main chains, and adopts aromatic side chains containing quaternary ammonium cationic groups, so that the membrane has higher mechanical properties, conductivity and chemical stability; and the present invention has higher surface roughness, so that the membrane can exert better performance in electrolytic water testing.

[0007] In order to solve the above technical problems, the present invention is implemented by the following technical solutions:

[0008] According to one aspect of the present invention, a high surface roughness anion exchange membrane based on radiation grafting is provided, and the chemical structure of the anion exchange membrane is as follows:

[0009]

[0010] The main chain of the anion exchange membrane is one of polyethylene (PE), polypropylene (PP), ethylene tetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride (PVDF), and polytetrafluoroethylene (PTFE); wherein QA + represents a quaternary ammonium cationic group; wherein the value of x is 100-35000, and the value of m is 1-500;

[0011] The surface roughness Ra of the anion exchange membrane is 500nm-5μm.

[0012] Furthermore, the quaternary ammonium cationic group is a trimethylamine cationic group.

[0013] According to another aspect of the present invention, there is provided a method for preparing the above-mentioned anion exchange membrane with high surface roughness based on radiation grafting, comprising the following steps:

[0014] (1) Preparation of high roughness precursor film:

[0015] Using one of polyethylene (PE), polypropylene (PP), ethylene tetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride (PVDF), and polytetrafluoroethylene (PTFE), a precursor film with high surface roughness is prepared by roller or solvent casting re-filming;

[0016] (2) Electron beam irradiation:

[0017] irradiating the precursor film with high surface roughness obtained in step (1) under electron beam radiation, and storing it at low temperature after irradiation;

[0018] (3) Grafted side chain:

[0019] First, chloromethyl vinylbenzene (VBC), a surfactant, and ultrapure water are added to a reactor, and an inert gas is introduced at room temperature to make the reactor an inert atmosphere environment, and at the same time, chloromethyl vinylbenzene (VBC) and the surfactant are uniformly mixed in the ultrapure water to form an emulsion;

[0020] Then, the irradiated film obtained in step (2) is added into the reactor, and an inert gas is introduced;

[0021] After passing inert gas for 0.5-2h, the reaction system is transferred to a water bath and reacted under heating;

[0022] After the reaction is completed, the film is washed with solvent A and then placed in a vacuum oven for drying to obtain a grafted intermediate film;

[0023] (4) Quaternization:

[0024] The grafted intermediate film obtained in step (3) is added to a quaternary ammonium cation solution for reaction, and after the reaction is completed, it is washed with solvent B to obtain an anion exchange membrane based on radiation grafting;

[0025] (5) Ion replacement

[0026] The anion exchange membrane based on radiation grafting synthesized in step (4) is immersed in a sodium chloride solution, and after washing with water, a Cl - Radiation-grafted anion exchange membranes for long-term storage in a wet state.

[0027] Furthermore, the pressing roller in step (1) refers to the process of passing pressure through the film at room temperature or at a high temperature of 50-600° C., so that its surface morphology changes and has a high surface roughness.

[0028] Furthermore, the solvent casting re-filming in step (1) refers to converting the film into a liquid state by melting or dissolving the film into a solvent at a high temperature above 80°C, and then solidifying the film into a film by casting on a surface with a certain roughness, so that the film has a high surface roughness.

[0029] Furthermore, the dose of the electron beam radiation in step (2) is 50-150 kGy.

[0030] Furthermore, the temperature of the cryopreservation in step (2) is less than or equal to -30°C.

[0031] Furthermore, the surfactant described in step (3) is 1-octyl-2-pyrrolidone (NOP).

[0032] Furthermore, in step (3), the volume ratio of chloromethyl vinylbenzene (VBC) to surfactant is 1-10:1.

[0033] Furthermore, the reaction in step (3) is carried out under heating, the reaction temperature should be 50-80°C, and the reaction time should be 4-24h.

[0034] Furthermore, the cleaning solvent A in step (3) is at least one of methanol, ethanol, isopropanol and deionized water.

[0035] Furthermore, the grafted intermediate film in step (4) is a film containing aromatic side chains of chloromethyl groups.

[0036] Furthermore, the quaternary ammonium cation solution in step (4) is a trimethylammonium solution with a concentration of 30-35 wt%.

[0037] Furthermore, the reaction in step (4) is carried out at room temperature for 24-48 hours.

[0038] Furthermore, the cleaning solvent B in step (4) is at least one of ethanol and deionized water.

[0039] The beneficial effects of the present invention are:

[0040] The present invention provides a high surface roughness anion exchange membrane based on radiation grafting and a preparation method thereof. A new type of anion exchange membrane material is synthesized by the process of radiation grafting, and the anion exchange membrane material has good mechanical strength, chemical stability and excellent electrochemical performance; and a method for enhancing the surface roughness of the anion exchange membrane based on radiation grafting is provided, so that it has stronger hydrophilicity and adhesion to the catalyst layer and a larger contact area with the catalyst layer, thereby having more excellent fuel cell and water electrolysis performance; in addition, since the radiation grafted high surface roughness anion exchange membrane prepared by the invention is different from the preparation method of traditional cast film, the present invention adopts the method of polymer precursor film modification to prepare it, because it is a heterogeneous reaction, during the reaction process, the high surface roughness film has a higher hydrophilicity, so that it is easier to combine with the reaction solution, so that it is easy to react evenly and reduce the difficulty of the reaction process. The overall process of the synthesis method in the present invention is relatively simple, the reaction conditions are mild, the reaction time is short, the cost is low, and it is easy to scale up production. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The following are scanning electron microscope (SEM) images of anion exchange membranes prepared in Example 1 and Comparative Example. ;

[0042] Figure 2 The hydroxide ion conductivity of the anion exchange membrane prepared in Example 1, wherein the horizontal axis is temperature, in units of ° C; the vertical axis is ion conductivity, in units of mS / cm.

[0043] Figure 3 The linear sweep voltammetric curves of the electrolysis performance of the anion exchange membranes prepared in Example 1 and Comparative Example, where the horizontal axis is the current in A / cm 2 ; The vertical axis is voltage, the unit is V.

[0044] Figure 4 These are pictures of the hydrophilic and hydrophobic angle tests of the anion exchange membranes prepared in Example 1 and Comparative Example. DETAILED DESCRIPTION

[0045] The following is a more detailed description of the specific implementation of the present invention in conjunction with the accompanying drawings and embodiments, so as to better understand the scheme of the present invention and its advantages in various aspects. It should be noted that the specific implementation methods and embodiments described below are only for the purpose of illustration, and are not intended to limit the present invention.

[0046] The present invention provides a high surface roughness anion exchange membrane based on radiation grafting, and the chemical structure of the anion exchange membrane is as follows:

[0047]

[0048] The main chain of the anion exchange membrane is one of polyethylene (PE), polypropylene (PP), ethylene tetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride (PVDF), and polytetrafluoroethylene (PTFE); wherein QA + represents a quaternary ammonium cationic group; wherein the value of x is 100-35000, and the value of m is 1-500;

[0049] The surface roughness Ra of the anion exchange membrane is 500nm-5μm.

[0050] For some preferred embodiments of the present invention, in S1, the quaternary ammonium cationic group is a trimethylamine cationic group.

[0051] At the same time, a method for preparing the above-mentioned anion exchange membrane with high surface roughness based on radiation grafting is provided, comprising the following steps:

[0052] (1) Preparation of high roughness precursor film:

[0053] Using one of polyethylene (PE), polypropylene (PP), ethylene tetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride (PVDF), and polytetrafluoroethylene (PTFE), a precursor film with high surface roughness is prepared by roller or solvent casting re-filming;

[0054] (2) Electron beam irradiation:

[0055] irradiating the precursor film with high surface roughness obtained in step (1) under electron beam radiation, and storing it at low temperature after irradiation;

[0056] (3) Grafted side chain:

[0057] First, chloromethyl vinylbenzene (VBC), a surfactant, and ultrapure water are added to a reactor, and an inert gas is introduced at room temperature to make the reactor an inert atmosphere environment, and at the same time, chloromethyl vinylbenzene (VBC) and the surfactant are uniformly mixed in the ultrapure water to form an emulsion;

[0058] Then, the irradiated film obtained in step (2) is added into the reactor, and an inert gas is introduced;

[0059] After passing inert gas for 0.5-2h, the reaction system is transferred to a water bath and reacted under heating;

[0060] After the reaction is completed, the film is washed with solvent A and then placed in a vacuum oven for drying to obtain a grafted intermediate film;

[0061] (4) Quaternization:

[0062] The grafted intermediate film obtained in step (3) is added to a quaternary ammonium cation solution for reaction, and after the reaction is completed, it is washed with solvent B to obtain an anion exchange membrane based on radiation grafting;

[0063] (5) Ion replacement

[0064] The anion exchange membrane based on radiation grafting synthesized in step (4) is immersed in a sodium chloride solution, and after washing with water, a Cl - Radiation-grafted anion exchange membranes for long-term storage in a wet state.

[0065] For some preferred embodiments of the present invention, the pressure roller in step (1) refers to the process of applying pressure to the film at room temperature or at a high temperature of 50-600° C., thereby changing its surface morphology and giving it a high surface roughness.

[0066] For some preferred embodiments of the present invention, the solvent casting re-filming in step (1) refers to converting the film into a liquid state by melting or dissolving the film into a solvent at a high temperature above 80°C, and then solidifying the film into a film by casting on a surface with a certain roughness, thereby forming a high surface roughness of the film.

[0067] According to some preferred embodiments of the present invention, the dose of the electron beam radiation in step (2) is 50-150 kGy.

[0068] In some preferred embodiments of the present invention, the temperature of the cryopreservation in step (2) is less than or equal to -30°C.

[0069] For some preferred embodiments of the present invention, the surfactant in step (3) is 1-octyl-2-pyrrolidone (NOP).

[0070] In some preferred embodiments of the present invention, the volume ratio of chloromethyl vinylbenzene (VBC) to surfactant in step (3) is 1-10:1.

[0071] In some preferred embodiments of the present invention, the reaction in step (3) is carried out under heating, the reaction temperature should be 50-80° C., and the reaction time should be 4-24 h.

[0072] In some preferred embodiments of the present invention, the cleaning solvent A in step (3) is at least one of methanol, ethanol, isopropanol and deionized water.

[0073] In some preferred embodiments of the present invention, the intermediate film after grafting in step (4) is a film containing aromatic side chains of chloromethyl groups.

[0074] In some preferred embodiments of the present invention, the quaternary ammonium cation solution in step (4) is a trimethylammonium solution with a concentration of 30-35 wt%.

[0075] In some preferred embodiments of the present invention, the reaction in step (4) is carried out at room temperature for 24-48 hours.

[0076] In some preferred embodiments of the present invention, the cleaning solvent B in step (4) is at least one of ethanol and deionized water.

[0077] Example 1

[0078] A high surface roughness anion exchange membrane based on radiation grafting is prepared by the following steps:

[0079] The ETFE film with low surface roughness (Ra≈300nm) was heated to 200°C and rolled with a metal roller with high roughness etched by laser, so that the precursor film was indented to increase the surface roughness. The surface roughness Ra was about 1.2μm as measured by laser microscopy.

[0080] The ethylene tetrafluoroethylene copolymer (ETFE) precursor film with high surface roughness obtained by roller pressing was irradiated under electron beam radiation with a radiation dose of 150 kGy, and was stored in dry ice after the irradiation.

[0081] 10 ml of chloromethylvinylbenzene (VBC), 2 ml of 1-octyl-2-pyrrolidone (NOP), and 188 ml of ultrapure water were added to a Schlenk tube, and argon gas was introduced for 30 minutes at room temperature. The liquid turned into a milky white uniform emulsion.

[0082] The ETFE precursor film was cut into 10*10 cm, placed in a Schlenk tube, and argon was continued to flow for 2 hours to allow the VBC and NOP droplets in the reaction solution to adhere to the film surface.

[0083] The vent tube was removed, the Schlenk tube was sealed, and the tube was heated in a water bath at 70°C under an inert gas atmosphere for 20 hours.

[0084] After the reaction, the liquid in the Schlenk tube was removed, isopropanol was added for washing, and the film was heated in a water bath at 70°C with stirring for 1 hour; the washed film was dried in an oven at 70°C for 4 hours to obtain a grafted intermediate film; its mass was weighed and increased by about 56.8%.

[0085] The grafted intermediate film was immersed in a trimethylamine solution (35wt%) and stirred at room temperature for 48 hours, and the film gradually changed from colorless and transparent to light yellow; it was washed with ultrapure water at 50°C and stirred for 1 hour to obtain an anion exchange membrane with high surface roughness based on radiation grafting.

[0086] The prepared anion exchange membrane was immersed in 1M NaCl solution for more than 24 hours to convert the anion into Cl - form.

[0087] The anion exchange membrane structure obtained in this example is Wherein, x and y are 0-5000, and m is 1-500. The surface roughness Ra is 1.2 μm as measured by laser microscope.

[0088] The dry anion exchange membrane after being dried in a vacuum oven at 60°C for 12 hours and the wet anion exchange membrane after being immersed in ultrapure water at room temperature for 12 hours were tested, and the water absorption rate was measured to be 64.31wt%. The universal material test showed that the mechanical strength was 33.71MPa and the elongation was about 66.35%. Moreover, in 80°C 1M KOH, the IEC loss in 30 days did not exceed 5%, and it has very excellent chemical stability.

[0089] Figure 2 The ionic conductivity test results at different temperatures of this embodiment are shown in Figure 1. The test was conducted using an ivum electrochemical workstation. The samples were immersed in ultrapure water. The ion form was OH - It can be seen from the results that the anion exchange membrane obtained in this embodiment has an extremely high ion conductivity, which can reach 229.1 mS / cm at 80°C, far exceeding the commercial anion exchange on the market.

[0090] Embodiment 2:

[0091] A high surface roughness anion exchange membrane based on radiation grafting is prepared by the following steps:

[0092] The same rolling method as in Example 1 was used to obtain a high surface roughness for the precursor film, with a roughness Ra≈1.2 μm.

[0093] The ethylene tetrafluoroethylene copolymer (ETFE) precursor film with high surface roughness obtained by roller pressing was irradiated under electron beam radiation with a radiation dose of 80 kGy, and was stored in dry ice after the irradiation.

[0094] 80 ml of chloromethylvinylbenzene (VBC), 16 ml of 1-octyl-2-pyrrolidone (NOP), and 1.502 L of ultrapure water were added to a Schlenk tube, and argon gas was introduced for 30 min at room temperature. The liquid turned into a milky white uniform emulsion.

[0095] The ETFE precursor film was cut into 25*170 cm, placed in a Schlenk tube, and argon was continued to flow for 2 hours to allow the VBC and NOP droplets in the reaction solution to adhere to the film surface.

[0096] The vent tube was removed, the Schlenk tube was sealed, and the tube was heated in a water bath at 70°C under an inert gas atmosphere for 20 hours.

[0097] After the reaction, the liquid in the Schlenk tube was removed, isopropanol was added for washing, and the film was heated in a water bath at 70°C with stirring for 1 hour; the washed film was dried in an oven at 70°C for 4 hours to obtain a grafted intermediate film; its mass was weighed and increased by about 56.8%.

[0098] The grafted intermediate film was immersed in a trimethylamine solution (35wt%) and stirred at room temperature for 48 hours, and the film gradually changed from colorless and transparent to light yellow; it was washed with ultrapure water at 50°C and stirred for 1 hour to obtain an anion exchange membrane with high surface roughness based on radiation grafting, with a size of about 40*200cm.

[0099] The prepared anion exchange membrane was immersed in 1M NaCl solution for more than 24 hours to convert the anion into Cl - form.

[0100] The dry anion exchange membrane after being dried in a vacuum oven at 60°C for 12 hours and the wet anion exchange membrane after being immersed in ultrapure water at room temperature for 12 hours were tested, and the water absorption rate was measured to be 59.02wt%; and through universal material testing, it was found that its mechanical strength was 36.12MPa and its elongation was about 72.15%; measured by the ivum electrochemical workstation, in ultrapure water, 80°C OH - In its molten form, the ionic conductivity is approximately 191.2 mS / cm.

[0101] Comparative Example:

[0102] An anion exchange membrane based on radiation grafting is realized by the following steps:

[0103] 1) An ethylene tetrafluoroethylene copolymer (ETFE) precursor film with a surface roughness Ra of 300 nm was irradiated under electron beam radiation with a radiation dose of 150 kGy, and was stored in dry ice after the irradiation.

[0104] 2) Add 10 ml of chloromethylvinylbenzene (VBC), 2 ml of 1-octyl-2-pyrrolidone (NOP), and 188 ml of ultrapure water into a Schlenk tube, and introduce argon gas for 30 min at room temperature. The liquid turns into a milky white uniform emulsion.

[0105] 3) Cut the ETFE precursor film into 10*10 cm, put it into a Schlenk tube, and continue to flow argon for 2 hours to allow the VBC and NOP droplets in the reaction solution to adhere to the film surface.

[0106] 4) Remove the vent tube, seal the Schlenk tube, and heat in a 70°C water bath under an inert gas atmosphere for 20 hours.

[0107] 5) After the reaction, the liquid in the Schlenk tube was removed, isopropanol was added for washing, and the film was heated in a water bath at 70° C. with stirring for 1 hour; the washed film was dried in an oven at 70° C. for 4 hours to obtain a grafted intermediate film; its mass was measured to increase by about 56.8%.

[0108] 6) The grafted intermediate film was immersed in a trimethylamine solution (35 wt%) and stirred at room temperature for 48 hours, and the film gradually changed from colorless and transparent to light yellow; ultrapure water was used to stir for 1 hour at 50°C for washing to obtain an anion exchange membrane with high surface roughness based on radiation grafting.

[0109] 7) Soak the prepared anion exchange membrane in 1M NaCl solution for more than 24 hours to convert the anion into Cl - form.

[0110] The surface roughness Ra of the anion exchange membrane obtained in this comparative example is about 300 nm.

[0111] Performance Test:

[0112] The anion exchange membranes based on radiation grafting prepared in the above examples and comparative examples were subjected to common electrochemical and water electrolysis performance tests. The electrochemical performance test data are shown in Table 1:

[0113] Table 1 Performance test results of anion exchange membranes based on radiation grafting prepared in Examples and Comparative Examples

[0114]

[0115] The above embodiments and comparative examples synthesized radiation-grafted anion exchange membranes with different radiation doses and surface roughness. It can be seen from Table 1 that the radiation intensity of Embodiment 1 and Embodiment 2 is different, thereby affecting the conductivity and IEC of the anion exchange membrane. By regulating the irradiation intensity, the number of quaternary ammonium cationic side chains can be changed, thereby changing the electrochemical properties of the anion exchange membrane based on radiation grafting. It can be seen from the results that the dose of electron beam radiation is in the range of 50-150KGy, and a higher radiation dose has better electrochemical properties; Embodiment 1 and the comparative example have differences in membrane surface roughness. From Table 1, Figure 3It can be seen that the surface roughness of the membrane has little effect on the electrochemical performance, but will have a greater impact on the water electrolysis performance. Membranes with higher surface roughness have better water electrolysis performance and are more suitable for application in water electrolysis to produce hydrogen.

[0116] The comparative example and Example 1 differ only in the surface roughness of the precursor film. Figure 1 This is a scanning electron microscope (SEM) image with a magnification of 650x. Figure 1 It can be seen that the comparative example and Example 1 have a large difference in microscopic morphology. Due to the use of a roller press method, the surface of Example 1 has protruding indentations. It can be seen from Table 1 that compared with Example 1, the comparative example and Example 1 have comparable film thickness, ion conductivity and mechanical properties, but have lower water absorption. Figure 3 This is the test result of hydrogen production by electrolysis of water. In the water electrolysis test, the anode uses 1mg / cm 2 IrO2 catalyst, cathode 1mg / cm 2 Platinum-carbon catalyst (20% Pt) was tested at 60°C, and the electrolyte was 1M KOH. From the test results, it can be seen that Example 1 has better water electrolysis performance, thus proving that the radiation-grafted anion exchange membrane with high surface roughness is more suitable for hydrogen production by water electrolysis; Figure 4 For the hydrophilicity test, it can be seen from the test results that the anion exchange membrane based on radiation grafting with high surface roughness has better hydrophilicity.

[0117] Although the preferred embodiments of the present invention have been described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments, which are merely illustrative and not restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms of specific changes without departing from the scope of protection of the invention and the claims, all of which fall within the scope of protection of the present invention.

Claims

1. A high surface roughness anion exchange membrane based on radiation grafting, characterized in that: The chemical structure of the anion exchange membrane is as follows: The main chain of the anion exchange membrane is one of polyethylene (PE), polypropylene (PP), ethylene tetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride (PVDF), and polytetrafluoroethylene (PTFE); wherein QA + represents a quaternary ammonium cationic group; wherein the value of x is 100-35000, and the value of m is 1-500; The surface roughness Ra of the anion exchange membrane is 500nm-5μm.

2. The anion exchange membrane with high surface roughness based on radiation grafting according to claim 1, characterized in that: The quaternary ammonium cationic group is a trimethylamine cationic group.

3. A method for preparing an anion exchange membrane with high surface roughness based on radiation grafting as claimed in any one of claims 1 to 2, characterized in that: The steps include: (1) Preparation of high roughness precursor film: Using one of polyethylene (PE), polypropylene (PP), ethylene tetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride (PVDF), and polytetrafluoroethylene (PTFE), a precursor film with high surface roughness is prepared by roller or solvent casting re-filming; (2) Electron beam irradiation: irradiating the precursor film with high surface roughness obtained in step (1) under electron beam radiation, and storing it at low temperature after irradiation; (3) Grafted side chain: First, chloromethyl vinylbenzene (VBC), a surfactant, and ultrapure water are added to a reactor, and an inert gas is introduced at room temperature to make the reactor an inert atmosphere environment, and at the same time, chloromethyl vinylbenzene (VBC) and the surfactant are uniformly mixed in the ultrapure water to form an emulsion; Then, the irradiated film obtained in step (2) is added into the reactor, and an inert gas is introduced; After passing inert gas for 0.5-2h, the reaction system is transferred to a water bath and reacted under heating; After the reaction is completed, the film is washed with solvent A and then placed in a vacuum oven for drying to obtain a grafted intermediate film; (4) Quaternization: The grafted intermediate film obtained in step (3) is added to a quaternary ammonium cation solution for reaction, and after the reaction is completed, it is washed with solvent B to obtain an anion exchange membrane based on radiation grafting; (5) Ion replacement The radiation-grafted anion exchange membrane synthesized in step (4) is immersed in a sodium chloride solution, and washed with water to obtain a radiation-grafted anion exchange membrane in which the counter ion form is Cl-, which is used for long-term storage in a wet state.

4. The method for preparing an anion exchange membrane with high surface roughness based on radiation grafting according to claim 3, characterized in that: The pressure roller in step (1) refers to the process of applying pressure to the film at room temperature or at a high temperature of 50-600°C, thereby changing its surface morphology and giving it a high surface roughness; the solvent casting re-filming in step (1) refers to the process of converting the film into a liquid state by melting or dissolving the film into a solvent at a high temperature of more than 80°C, and then solidifying the film by casting on a surface with a certain roughness, thereby giving the film a high surface roughness.

5. The method for preparing an anion exchange membrane with high surface roughness based on radiation grafting according to claim 3, characterized in that: The dose of the electron beam radiation in step (2) is 50-150 kGy; the temperature of the cryopreservation in step (2) is less than or equal to -30°C.

6. The method for preparing an anion exchange membrane with high surface roughness based on radiation grafting according to claim 3, characterized in that: The surfactant described in step (3) is 1-octyl-2-pyrrolidone (NOP); the volume ratio of chloromethyl vinylbenzene (VBC) to the surfactant described in step (3) is 1-10:

1.

7. The method for preparing an anion exchange membrane with high surface roughness based on radiation grafting according to claim 3, characterized in that: The reaction in step (3) is carried out under heating, the reaction temperature should be 50-80°C, and the reaction time is 4-24h; the cleaning solvent A in step (3) is at least one of methanol, ethanol, isopropanol, and deionized water.

8. The method for preparing an anion exchange membrane with high surface roughness based on radiation grafting according to claim 3, characterized in that: The grafted intermediate film in step (4) is an aromatic side chain film containing chloromethyl groups; the quaternary ammonium cation solution in step (4) is a trimethylammonium solution with a concentration of 30-35 wt %; the reaction in step (4) is carried out at room temperature for 24-48 hours.

9. The method for preparing an anion exchange membrane with high surface roughness based on radiation grafting according to claim 3, characterized in that: The cleaning solvent B in step (4) is at least one of ethanol and deionized water.

Citation Information

Patent Citations

  • Membrane-electrode assembly for fuel cell, method of preparing same, and fuel cell system cpmrising same

    CN101136480A

  • Method for preparing cation exchange membrane with monovalent preferential separation function

    CN102935389A

  • High-viscidity modified PI film

    CN106279746A

  • Preparation method of ion exchange membrane

    CN111318191A

  • Reinforcing material prepared from fluorine-containing ionic polymer and application of reinforcing material in proton exchange membrane

    CN115976683A